Civil Law: A Review Literature of Indonesian University Student Perspectives - Arifin, Muhammad (Advances in Social Sciences Research Journal, 2020)
Indonesia has one of the world’s most legally diverse and complex civil law systems in the world. The country’s civil code was inherited from the Dutch during the colonization era. The aim of this study was to examine the perceptions of Indonesian students about their country's civil law. It was established that no particular study had explored the issue under investigation. As a result, the researcher developed a novel conceptual framework to facilitate the collection and analysis of relevant data from books and journal articles. Specifically, a combination of the Grounded Theory (GT) research approach and thematic analysis was used as the methodology for gathering and evaluating data. The findings revealed that Indonesian students think that their country’s civil code does not effectively meet the various needs of the local communities. Moreover, the research also confirmed Indonesian students lack interest and expertise to research about the nation’s civil law. It is recommended that to improve the reliability and validity of the present study, future researchers should collect primary data by interviewing and administering questionnaires to students.